2016
DOI: 10.1590/s0100-83582016340400017
|View full text |Cite
|
Sign up to set email alerts
|

Application of Post-Emergence ALS Inhibitor Herbicides Associated or Not to Glyphosate in RR/STS Soybean

Abstract: -The aim of this study was to evaluate the selectivity of ALS inhibitor herbicides, applied isolated and associated with glyphosate in post-emergence of soybean cultivar presenting the RR/STS technologies. The experimental design was a randomized block with four replications and ten treatments. The treatments consisted of the application of glyphosate and ALS inhibitors herbicides, isolated and associated with glyphosate. The application of treatments occurred in V4 stage of plant development. The evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…The percentages of injury varied from 24 to 45, but in general, no reductions in yield were observed during the four years of cultivation. Silva et al (2016) found symptoms of injury of at most 5.5% for nicosulfuron application (60 g a.i. ha -1 ) in post-emergence (V4) alone or in combination with glyphosate (960 g a.e.…”
Section: (A) (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of injury varied from 24 to 45, but in general, no reductions in yield were observed during the four years of cultivation. Silva et al (2016) found symptoms of injury of at most 5.5% for nicosulfuron application (60 g a.i. ha -1 ) in post-emergence (V4) alone or in combination with glyphosate (960 g a.e.…”
Section: (A) (B)mentioning
confidence: 99%
“…ha -1 (Albrecht et al, 2017). According to Silva et al (2016), the application of nicosulfuron (60 g a.i. ha -1 ) caused no injury and did not affect RR/STS soybean yield.…”
Section: Introductionmentioning
confidence: 99%
“…ha -1 ) and glyphosate (960 g a.e. ha -1 ), without crop injury and reductions in variables related to agronomic performance (SILVA et al, 2016). Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…: chlorimuron-ethyl) e das sulfonanilidas (ex. : cloransulam) são seletivos para a soja em pós-emergência (SILVA et al, 2016). Em áreas que ocorrem simultaneamente plantas daninhas poáceas e eudicotiledôneas, a mistura de herbicidas apresenta vantagens sobre o ponto de vista operacional.…”
Section: Introductionunclassified